PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MENGGUNAKAN APLIKASI QUIZIZZ UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Junaidi, Junaidi; Taufiq, Taufiq; Mirunnisa, Mirunnisa; Maulina, Suci; Musriandi, Riki; Farisya, Putroe (Jurnal Dedikasi Pendidikan, 2025)
This study aims to improve problem-solving skills in the application of the Quizizz application. The model used in this study is Problem Based Learning (PBL), a student-centered learning model where students must be able to solve mathematical problems. The Quizizz application helps students in solving mathematical problems, and helps teachers design online quizzes, discussions, or surveys. This research is a quantitative study with a quasi-experimental method. The research design used in this study is Pre-test Post-test Control Group Design. The sample of this study consisted of 60 students selected by purposive sampling. Data collection instruments in this study were carried out with a final test and data processing using an independent sample t-test. The results of data analysis showed that the average value of the experimental class was higher, namely 80.13 and the control class 70.04. The results of hypothesis testing obtained that mathematics learning with the Problem Based Learning model using the Quizizz Application can improve mathematical problem-solving skills in students of SMPN 1 Simpang Tiga